Design and Production of Heartbeat Counter for Medical Application - Akpan, W.A.; Nyaudo, I.I.; Obot, O. W. (Engineering And Technology Journal, 2024)
Heartbeat pulse measurement is an important medical practice used to determine the health status of an individual. This research was concerned on the design and production of heartbeat pulse counter for medical applications with specific features. The device senses and monitors the heartbeat rate whenever a fingertip is placed on the pulse sensor, the pulse sensor is a plug and play device which is detachable from the Arduino Uno board, the Arduino Uno receives and calculates this data and the result displayed on the 16X2 LCD display based on the written codes. It has the features for initial display, showing system on and when a finger is placed, it readily displays heartbeat rate detected and presents the pulse rate of the individual. Its design and production was achieved and used to test the heartbeat of many persons. Further work is required to incorporate GSM module with the capability of sending text message and cloud hosting of the medical data of an individual.